Prebiotics, probiotics and postbiotics for sustainable poultry production. Issue 4 (2nd October 2021) - Reuben, Rine Christopher; Sarkar, Shovon Lal; Roy, Pravas Chandra; Anwar, Azraf; Hossain, M. Anwar; Jahid, Iqbal Kabir
ABSTRACT: Globally, poultry production has been an integral part of human activities, providing a major source of livelihood and food to humans. The continuous increase in the world population with an attendant rise in the demand for safe poultry products requires a global strategy for sustainable poultry production. With growing concerns over antimicrobial resistance, abolition or reduction in the use of antibiotic growth promoters (AGPs), and rising consumer demand for chemical or antibiotic-free products, identifying and applying safe, natural and economical alternatives including prebiotics, probiotics and postbiotics for sustainable poultry production has become imperative. The beneficial effects of the dietary inclusion of prebiotics, probiotics and postbiotics as AGP alternatives in poultry production include improved poultry health, growth performance and feed efficiency. Generally, the mechanisms through which prebiotics, probiotics and postbiotics exert beneficial effects on poultry include competitive exclusion and antagonism of pathogens, modulation of intestinal microbiota, production of antimicrobial substances, stimulation of immune system, and enhancement of nutrient digestibility and intestinal morphology development. The properties and beneficial effects of these emerging alternatives suggest their contribution to the improvement of poultry health, through the stimulation of diverse physiological functions (although not entirely elucidated) with better growth performance and feed efficiency. This review discusses the concept, impacts and mechanisms of the application of prebiotics, probiotics and postbiotics in sustainable poultry production. Their general acceptance and application in the poultry industry will undoubtedly result in more sustainable, safe and economic poultry production for feeding the world.